Sifat Fisika dan Mekanika Papan Laminasi Bambu Petung (Dendrocalamus Asper) dengan Susunan Bilah Ke Arah Lebar - Febriana Wulandari; Habibi; Radjali Amin (HUTAN TROPIKA, 2023)
Bamboo that has the potential to be developed as a laminated board is petung bamboo. Bamboo petung can be made of laminated boards because it has thick stem walls (10 mm-30 mm), thick stem walls will save the use of adhesives. The requirements for making bamboo laminated boards are straight trunks, 3 to 5 years old and not attacked by pests and diseases. For the feasibility of using petung bamboo as a laminated board, it is necessary to test the physical and mechanical properties of the petung bamboo laminated board. Physical properties are needed to determine the dimensional stability of the resulting board and mechanical properties are needed to determine the ability of the board to withstand loads. This research will look at the strength of the physical and mechanical properties of laminated board based on the arrangement of the blades towards the width and the effect of laur weight on the physical and mechanical properties of petung bamboo laminated board. The research method used in this study used an experimental method with a non-factorial Completely Randomized Design (CRD) experimental design with two treatments (flour weight). The study of laminated boards with the arrangement of the blades towards the width resulted in the following physical and mechanical properties: moisture content: 13.746%, density: 0.418 gram/cm3, thickness sweeling: 2.325%, MoE: 15120.226 kgf/cm2 and MoR: 354.943 kgf/ cm2. All tests of physical and mechanical properties had no significant effect on the adhesive mass except for the thickness shrinkage test. Based on the value of the strength class of the laminated board, the bamboo petung laminated board with the arrangement towards the width is included in the strong class III which can be used as building materials such as door frames, windows, panels, household furniture and wood industries.